Pengolahan Data Penerima Kartu Indonesia Sehat Menggunakan Transaction Processing System - Dede Wira Trise Putra; Syaiful Rahman (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Healthy Indonesia Card (KIS) is a government aid whose recipient data is submitted to each region for processing. The data processing of the Healthy Indonesia Card (KIS) uses the bookkeeping method. The problems and obstacles faced are the occurrence of file stacking, file damage, difficulties in finding data and the occurrence of data duplication in the data input process. These problems lead to errors in the use of data by interested parties. Based on the existing problems, a Transaction Processing System (TPS) was designed to facilitate data processing and minimize errors and errors. The designed Transaction Processing System (TPS) is a web-based information system. The use of this system can make data stored properly and regularly. And if there is an addition and deletion of data can be done directly by the user concerned. Transaction Processing System for processing population data can provide convenience for users in inputting and processing data. The designed system has been built and tested based on user requirements.